Sustainable Lean Procurement and Contract Management in Oil and Gas Industry - Umasekar, Vijayakumar (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Lean methodologies have enabled numerous businesses to enhance their processes, reduce inventory levels, and improve ergonomics. Additionally, lean has allowed organizations to adapt their technologies and keep pace with necessary advancements. However, despite the numerous benefits it offers and the implementation of lean thinking and procurement in the oil and gas industry, companies have frequently encountered challenges related to the timely delivery of materials and services. This research aimed to understand how the oil and gas industry implements lean procurement practices, investigate the relationship between lean procurement and supply chain performance, and identify the challenges faced by the industry in implementing lean procurement. The study employed a case study approach, focusing on the oil and gas industry's command centre as the target population. Through stratified random sampling, a sample of 37 leaders from the oil and gas industry was selected, representing 20% of the target population. Secondary data sources included the industry's annual reports and financial summaries, while primary data was collected through questionnaires. The quantitative data gathered for this research was analysed using the Statistical Package for the Social Sciences (SPSS) version 20, employing both descriptive and inferential statistical techniques. Descriptive statistics components included percentages, standard deviation, frequency, and mean. Data presentation was facilitated through tables, charts, and diagrams. A narrative framework was utilized to present the results of the content analysis conducted on the qualitative data. Additionally, regression analysis was employed to further understand the relationship between lean procurement and supply chain performance. The study results demonstrated the existence of a positive and significant correlation between lean procurement and supply chain performance. Furthermore, the study indicated that the oil and gas industry utilized lean procurement strategies such as electronic procurement, 5S, comprehensive quality management, continuous improvement, supplier-firm collaboration, the pull system, and employee involvement and empowerment. The study's findings suggest that the oil and gas industry should foster relationships with service providers staffed by knowledgeable personnel capable of efficiently implementing lean procurement practices. By doing so, the industry can effectively address the challenges associated with timely material delivery and optimize its supply chain performance.